2012
DOI: 10.1007/s12070-012-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Nasal Mucociliary Activity After Septoplasty and External Septorhinoplasty

Abstract: The aim of this study was to evaluate the nasal mucociliary activity after septoplasty (SP) and external septorhinoplasty (eSRP). Twenty patients who had SP operation (group 1) and 15 patients who had eSRP operation (group 2) were enrolled in the study. On each case, mucociliary clearance (MCC) measurement was performed by saccharine test before surgery, and on the first and third months of postoperative period. Saccharine clearance time (SCT) of 28 healthy volunteers were measured to establish control values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…10 Sakallıoglu et al declared that septoplasty operation positively affects the MCC mechanism. 11 We also found MCC time significantly decreased after septoplasty for both the groups. Improvement in MCCt after septoplasty is independent from the age factor.…”
Section: Resultssupporting
confidence: 52%
“…10 Sakallıoglu et al declared that septoplasty operation positively affects the MCC mechanism. 11 We also found MCC time significantly decreased after septoplasty for both the groups. Improvement in MCCt after septoplasty is independent from the age factor.…”
Section: Resultssupporting
confidence: 52%
“…The purpose of this study was to demonstrate the changes of the mucociliary clearance in particular diseases, or to highlight the possible risk factors for its prolonged duration [6][7][8][9] . Rhinitis and chronic rhinosinusitis have an undeniable role in the mucociliary clearance decreased performance, according to a US In a study on patients with deviated septum, who underwent septoplasty intervention, it has been shown that this pathology has a direct effect on the mucociliary clearance and that surgery has good effects in restoration of the mucociliary function in affected patients 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The same procedure was repeated on other side of nose after a gap of 30 minutes. 15,16 Pre-operative preparations were same for all the 40 patients and all cases were done under general anesthesia. Twenty of the 40 patients had deviated nasal septum who underwent endoscopic septoplasty, and the rest 20 had deviated septum and compensatory inferior turbinate hypertrophy who underwent endoscopic septoplasty with partial inferior turbinectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were observed by Oner et al in their study of evaluation of nasal mucociliary activity after septoplasty. 15 Yigit et al investigated the effect of septoplasty on NMC time using radioscintigraphy. In their study the NMC time preoperatively was significantly higher than the control group.…”
mentioning
confidence: 99%